Plant Closure and Marital Dissolution - Mari Rege; Kjetil Telle; Mark Votruba (Statistics Norway, Research Department, 2007)
We estimate the effect of plant closure on divorce using a panel data set comprising more than 80,000 married couples in Norway. Plant closure substantially increases the likelihood of marital dissolution of workers in affected plants. The marriages of husbands originally employed in plants that closed between 1995 and 2000 were 11 percent more likely to be dissolved by 2003 than comparable marriages of husbands in stable plants. Additional analyses suggest that the effect of plant closure on divorce is not due to unexpected reduction in earnings. The results are, however, consistent with role theories, in which the husband's attractiveness declines if he fails to fulfill a traditional role as a breadwinner.
Keywords: J12; J63; J65; 330; marital dissolution; divorce; new information; shock; plant closure; plant downsizing; displacement